Platelet-Rich Plasma Is an Equal Alternative to Surgery in the Treatment of Type 1 Medial Epicondylitis. Issue 3 (25th March 2020) - Bohlen, Hunter L.; Schwartz, Zachary E.; Wu, Victor J.; Thon, Stephen G.; Finley, Zachary J.; O'Brien, Michael J.; Savoie, Felix H.
Background: Medial epicondylitis (ME) is characterized as an overuse injury resulting in pathological alterations of the common flexor tendon at the elbow. Platelet-rich plasma (PRP) has recently become of interest in the treatment of musculoskeletal conditions as an alternative to operative management. Purpose: To compare the outcomes of recalcitrant type 1 ME after treatment with either PRP or surgery. Study Design: Cohort study; Level of evidence, 3. Methods: To compare the 2 methods of treatment, we performed a retrospective review of 33 patients diagnosed with type 1 ME from 2006 to 2016 with a minimum clinical follow-up of 1 year who had failed an initial nonoperative treatment program of injections, medication, topical creams, and/or physical therapy. Overall, 15 patients were treated with a series of 2 leukocyte-rich PRP injections, and 18 patients were treated with surgery. Outcome measures included time to pain-free status, time to full range of motion (ROM), the Mayo Elbow Performance Score (MEPS), and the Oxford Elbow Score (OES). Each patient had at least 1-year follow-up. They were then contacted by telephone to determine final scores at a minimum 2-year follow-up. Unsuccessful outcomes were determined by the Nirschl grading system and failure to reach pain-free status, achieve baseline ROM, or return to previous activity. Results: The mean final follow-up was 3.9 years. A statistically significant improvement was noted in both time to full ROM (42.3 days for PRP vs 96.1 days for surgery; P < .01) and time to pain-free status (56.2 days for PRP vs 108.0 days for surgery; P < .01). Successful outcomes were observed in 80% of patients treated with PRP and 94% of those treated operatively ( P = .37). No significant difference was found in return-to-activity rates, overall successful outcomes, MEPS scores, or OES scores. Conclusion: In this case series, the use of PRP showed clinically similar outcomes to those of surgery in recalcitrant type 1 ME. PRP can be considered as an alternative to surgery in the treatment of recurrent ME, with an earlier time to full ROM and time to pain-free status compared with surgery.